2022
DOI: 10.1029/2022wr032031
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Assessment of Floodwater Depth Estimation Models in Semiarid Regions

Abstract: Simple models continue to be important for continental‐scale floodwater depth mapping due to the prohibitively expensive cost of calibrating and applying hydrodynamic models. This paper investigates the accuracy of three simple models for floodwater depth estimation from remote sensing derived water extent and/or Digital Elevation Models (DEMs) in semiarid regions. The three models are Height Above Nearest Drainage (HAND; Nobre et al., 2011, https://doi.org/10.1016/j.jhydrol.2011.03.051), Teng Vaze Dutta (TVD;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 89 publications
2
14
0
Order By: Relevance
“…FwDET calculates water depth by first extracting boundary elevation of the flood extent from a DEM, interpolating water surface elevation using the boundary elevation, then subtracting the ground elevation from the interpolated surface elevation. The interpolation method used in this version was the Thin Plate Spline, which provided a smoother surface and overcome some of the known caveats of linear interpolation used in the previous version of FwDET 16 . Input data borders and the boundaries of areas without data (fully cloud covered through the two-month period) were not included as points in the interpolation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…FwDET calculates water depth by first extracting boundary elevation of the flood extent from a DEM, interpolating water surface elevation using the boundary elevation, then subtracting the ground elevation from the interpolated surface elevation. The interpolation method used in this version was the Thin Plate Spline, which provided a smoother surface and overcome some of the known caveats of linear interpolation used in the previous version of FwDET 16 . Input data borders and the boundaries of areas without data (fully cloud covered through the two-month period) were not included as points in the interpolation.…”
Section: Methodsmentioning
confidence: 99%
“…Teng et al . 16 conducted a comprehensive assessment of floodwater depth estimation models in semi-arid regions and found that the Floodwater Depth Estimation Tool (FwDET), first developed by Cohen et al . 17 was the most suitable approach for this region.…”
Section: Background and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…
The recently released two monthly maximum water depth maps by Teng et al, (2023) provide opportunities for scientists to examine the relationship between hydrological and ecological processes. The depth maps provide a consistent spatial estimate of flood water depth across the Murray-Darling Basin (MDB) over the past 35 years.
…”
mentioning
confidence: 99%